Deformações e modo de ruptura em prismas de blocos de concreto: análise experimental com extensometria e correlação de imagem - Schossler, Rodrigo Teixeira (2019)
Evaluating deformations that constituent materials of structural masonry suffer has been the focus of researchers around the world. Structural masonry is a structural system that has a behavior difficult to predict because the materials, when they are analyzed separately, have distinct characteristics and compositions. Current Brazilian standards for structural masonry do not take into account the influence of mortar on the ultimate strength and failure mode of the wall in a direct manner. Considering that properties of the block and the mortar can influence the behavior of the masonry, the present work seeks to analyze deformations and the failure mode of concrete block prisms that have different block and mortar resistances. This study analyzed two types of concrete blocks having their net area strengths of 19.89 MPa and 11.39 MPa, respectively. Each type of block was combined with two laying mortar resistances equivalent to a characteristic block strength in the net area of 0.30 and 0.70. For this reason, compression tests were performed on instrumented prisms to analyze the behavior and specific deformation separately of each material used in the prism set, and they were also filmed to obtain the failure mode through digital image correlation. The blocks separately were also instrumented and filmed, verifying their mechanical behavior when subjected to axial compression and their correlation when used as prism set. In addition, compression tests were performed on instrumented proof bodies of the bedding mortar used for the prism molding, with the purpose of finding the stress-strain curve of the material and verifying the onset of non-linearity, as well its correlation when used as the prism set. From the analysis of the results, it was observed the influence of the proportion that exists between the compressive strength of mortar and block on the strength and failure mode of concrete prisms subjected to compression. It was verified that the mortar resistance did not interfere in the ultimate resistance of the prisms, but triggering the failure mode process.